AN EMPIRICAL ASSESSMENT OF ADOPTION AND INNOVATION OF THE PORTABLE BANKING TECHNOLOGY IN KENYA - Ahmed, Eltigani M. A. (Indian Journal of Finance and Banking, 2021)
The study investigated the appropriateness of innovation diffusion in understanding and explaining the adoption rate and acceptability of portable bank technology in Kenya through the assessment of the factors that influence the adoption of portable banking technology. The study employed a sample of 115 portable bank technology adopters based on a purposive sampling technique and tested the five attributes of innovations, namely relative advantage, compatibility, complexity, trialability, and observability. The study found that relative advantage, compatibility, Trialability, and observability positively impact adoption. Trialability and complexity were found to have a lesser significant effect on adoption. Complexity hurts adoption. More specifically, the regression model revealed that compatibility is the most significant determinant of adopting portable bank technology with t=4.21 and p ≤ 0.001. Trialability has a significant positive impact on adoption with t= 4.27 and p ≤ 0.001. Observability has a high explanatory value with t = 4.45 and p ≤ 0.001. Relative advantage has returned a positive explanatory coefficient at t=4.50 and p ≤ 0.001. Finally, Complexity had no significant impact on the adoption of portable banking technology. The study has uncovered useful trends in portable bank technology adoption in Kenya. The study recommended that future research should focus on broader variables and carry out comparative studies on both homogeneous and heterogeneous settings to gauge the net effect of technical attributes on technology adoption. JEL Classification Codes: D14, G21, G23, O13, O14, Q55.